ASSESSING SCLERACTINIAN CORALS AS RECORDERS FOR PALEO-PH: EMPIRICAL CALIBRATION AND VITAL EFFECTS - Hönisch B.; Hemming N.G.; Grottoli A.G.; Amat A.; Hanson G.N.; Bijma J. (My University, 2004)
Laboratory experiments on the branching, symbiont-bearing coral genus Porites and Acropora have been carried out to determine the dependence of the skeletal boron isotopic composition (δ11B) on the pH of seawater. The results show a clear relationship similar to previously established empirical calibrations for planktonic foraminifera and inorganic calcite. A -0.6‰ offset exists between P. cylindrica and A. nobilis which is systematic over the pH range of 7.7– 8.2. To test whether the δ11B of coral skeletons changes with physiological processes such as photosynthesis and respiration, corals were grown along a depth transect in their natural environment and under controlled conditions in the laboratory at varying light intensities and food supply. Although we also observe an isotopic offset between P. compressa and Montipora verrucosa, neither experimental treatment systematically changed the δ11 B of the two species. These findings are encouraging for using the boron isotope paleo-pH proxy in corals, because it appears that seawater pH is the dominant control on the boron isotopic composition in corals.